2020
DOI: 10.1186/s12903-020-1007-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of air-polishing on surface roughness of composite dental restorative material – comparison of three different air-polishing powders

Abstract: Background: Increased composite roughness enhances bacterial adhesion and discoloration, thus increasing the risk of gingival inflammation and secondary caries. Concerns about detrimental effects of sodium bicarbonate on surface roughness influenced the development of less abrasive powders: a glycine-based powder and an erythritolbased powder, additionally -sodium bicarbonate-based powder of reduced grain size. However, there is limited evidence on effects of these materials on the surface of dental fillings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 26 publications
1
24
1
4
Order By: Relevance
“…This contradicts a previous study showing that glycine powder resulted in significantly less substance loss when compared with sodium bicarbonate [8]. Also, the finding of this study showed no significant difference in the wear depth between glycine and erythritol, which is in accordance with a previous study indicating that these powders have a similar surface-damaging potential [24].…”
Section: Sultan Et Al (contrasting
confidence: 92%
“…This contradicts a previous study showing that glycine powder resulted in significantly less substance loss when compared with sodium bicarbonate [8]. Also, the finding of this study showed no significant difference in the wear depth between glycine and erythritol, which is in accordance with a previous study indicating that these powders have a similar surface-damaging potential [24].…”
Section: Sultan Et Al (contrasting
confidence: 92%
“…There seems to be no dearth of reports incriminating sodium bicarbonate polishing powder for severe root damage within short applications. [ 15 16 17 ] It has also been contraindicated in cases with sodium restricted diet hypertension and renal insufficiency etc.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating the effect of air-abrasive powders on teeth and dental materials showed that sodium bicarbonate powder increases the roughness of tooth and composite surfaces. Glycine and erythritol also have surface changing effects, but they are less abrasive (26,36,37). Glycine powder causes the least surface damage during the removal of plaque on different restorative materials (38).…”
Section: Discussionmentioning
confidence: 99%